The reality shock at the beginning of a career: What factors can mitigate it? - Fonçatti, Maria Cecília; Morelatti, Maria Raquel Miotto (Debates em Educação, 2026)
This text presents a segment of the postdoctoral research titled "Reflections of the Lesson Study Experience During Undergraduate Education on the Practice of Mathematics Teachers". The study involved seven mathematics teachers with 1 to 5 years of teaching experience who, during their initial teacher training (Mathematics Degree), participated in the Pedagogical Residency Program (RP), engaging in an intervention based on Lesson Study in 2019. Considering that, in theory, the intervention based on Lesson Study could provide experiences that could mitigate the reality shock often experienced at the beginning of a teaching career, individual interviews were conducted with these seven teachers to determine whether this goal was achieved and whether other factors besides participation in the intervention contributed this outcome. The data analysis, conducted using discursive textual analysis, revealed that the reality shock was mitigated not only by the experience with Lesson Study but also by participation in the RP in general, as well as by engagement as teachers in the Junior Scientific Initiation Program of the Brazilian Public Schools Mathematics Olympiad (PIC/OBMEP) and the Institutional Program for Teaching Initiation Scholarships (PIBID), which some interviewees had experienced. This highlights the importance of extracurricular activities during undergraduate studies, as they provide meaningful school experiences and effectively contribute to alleviating the reality shock.